Rancang Bangun Sistem Informasi Pengadaan Bahan Baku Di PT. Derma International Bandung - Kuwat Santoso (Masoem University, 2021)
The Information System for Raw Material Procurement at PT.Derma International is still not well computerized which causes data inconsistencies on raw materials and this also slows down the process of data collection of Raw Materials. The design of this Raw Material Procurement Information System uses a design tool in the form of a System Development Life Cycle (SDLC). The diagrams used include: Data Flow Diagrams, Structural Charts, Flow Maps, and E-R Diagrams. The development of this application uses Visual Studio 2010 which is desktop-based and MySQL as a database with a good security level and supports flexible transactionals. After going through several stages of analysis and design, the Raw Material Procurement Information System is expected to provide convenience in data collection and reporting, minimize data errors and provide smooth production processes for the company